Caveat RAPtor : Regulation in Resource Allocation and Purchasing - Feeley, Frank G. (World Bank, Washington. DC, 2013)
This paper examines the effect that existing and proposed laws and regulations can have on the feasibility and effectiveness of arrangements for resource allocation and purchasing for the health sector in developing and transitional economies. The paper reviews effects of laws and regulations on: the medical benefits purchased, .the choice of medical provider, and .the transaction in which care is provided. Specific reference is made to recent experience in Russia, South Africa, Chile, and the Philippines, as well as possible precedents from more developed countries. Categories of law and regulation discussed include: provider licensing, monopoly and competition legislation, liability for professional negligence, mandated benefits and permitted exclusions, antidiscrimination laws, appeals procedures and other methods of asserting patient entitlement, rate setting and prohibitions on unauthorized provider charges, capacity controls and purchaser discretion in selecting providers, and patient confidentiality and collection of payment-related data.